Morphological description and histological structure of olfactory organ in Adult local chicken(Gallus domesticus) - Ashwaq A. Hussian; Hussain A. M. Dauod (Journal of Madenat Alelem University College, 2011)
The Morphological description and histological structure of olfactory organ in local chicken have been studied. The Results of the present study showed that olfactory organ in local chicken is composed of two nasal chambers which are small conical in their shape, and located at the dorsal surface of the head beneath the eye level. Nasal chambers are separated by nasal septum. The nasal chambers open to the outside through the external nares and to the oral cavity through the internal nares. On the other hand results revealed that each of the nasal cavity contains three chonchae which represented by rosteral nasal choncha,middle nasal choncha and caudal nasal choncha. The first and the second are scroll in their shape while the third is small spherical. Study of the histological structure of olfactory organ in local chicken showed that the tissue surrounded the external nares is keratinized stratified squamous epithelium,which extends above the nares edges to the beginning of the nasal cavity and forming the vestibular epithelium. The respiratory epithelium is found in the respiratory region of the nasal cavity. The olfactory epithelium represented by pseudostratified columnar epithelium which consist of three kind of cells: basal cells , supporting cells in and receptor cells